Islamic reformism in the Netherlands East Indies : the role and thought of Abd Allah B. Alawi B. Abd Allah al-Attas (1844-1929) - Alatas, Alwi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The Purpose of this study is to examine the thought and role of Sayyid cAbd Allah b. cAlawi al-cAttas (1844-1929) in the Netherlands East Indies and with particular emphasis on his financial and intellectual contributions to the development of Islamic reformism in the region. This study is based on a variety of primary and secondary source that enabled the researcher to highlight various aspects of Sayyid cAbd Allāh's life and career, and his involvement in intellectual Islamic discourse that took place in the 19th and the first part of the twenties centuries. A Historical and textual analysis method was adopted by the researcher so as to examine the sources of the study, and put the contributions of Sayyid cAbd Allah in their historical context. The overall output of the study is that the case of Sayyid cAbd Allah offers a better understanding of the features of the 19th and 20th century Islamic reformism, and the roles of the Hadhrami community in disseminating the idea of islāh and tajdīd in the Netherlands East Indies. It also paves the way for further biographical works on the distinguished figures of the Hadhrami community who remarkably contributed to the spread of Islamic reformism in the Malay world.